2017
DOI: 10.1249/mss.0000000000001313
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Physical Activity, Body Composition, and Physical Fitness in Preschoolers

Abstract: Higher VPA and MVPA at the age of 4.5 yr were significantly associated with higher FFMI and better physical fitness at 12-month follow-up. Our results indicate that promoting high-intensity PA at young ages may have long-term beneficial effects on childhood body composition and physical fitness, in particular muscular strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
108
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(124 citation statements)
references
References 34 publications
11
108
3
2
Order By: Relevance
“…Our results showed that replacing IT for LPA is associated with improved body composition changes (body fat and muscle mass), although the greatest bene t has been observed with MVPA. Similar results have been observed in previous cross-sectional research in adults [32] and in longitudinal studies performed with children [48,49]. Therefore, the present results build on previous knowledge in other populations and indicate that replacing IT with any other activity behaviour has a bene cial impact on body composition in older adults with an incremental effect according to the intensity level.…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that replacing IT for LPA is associated with improved body composition changes (body fat and muscle mass), although the greatest bene t has been observed with MVPA. Similar results have been observed in previous cross-sectional research in adults [32] and in longitudinal studies performed with children [48,49]. Therefore, the present results build on previous knowledge in other populations and indicate that replacing IT with any other activity behaviour has a bene cial impact on body composition in older adults with an incremental effect according to the intensity level.…”
Section: Discussionsupporting
confidence: 91%
“…For example, a previous cross‐sectional study has shown that objectively measured MVPA was not associated with markers of adiposity in girls aged 3 to 5 years, while a positive association was found for boys . In addition, another study has shown that MVPA at 4.5 years was not associated with adiposity at 5.5 years .…”
Section: Discussionsupporting
confidence: 86%
“…For example, a previous cross-sectional study has shown that objectively measured MVPA was not associated with markers of adiposity in girls aged 3 to 5 years, while a positive association was found for boys (24). In addition, another study has shown that MVPA at 4.5 years was not associated with adiposity at 5.5 years (25). The prevalence of children meeting the 24-h movement guidelines in the present study is similar to one previous study (18.4% vs. 17.1%) (12), and substantially higher than the mean of 7.2% (range 2.0-14.0% dependent on country of study) presented in a study with data from 12 different countries (13).…”
Section: Discussionmentioning
confidence: 96%
“…Physical fitness assessments were performed according to the validated PREFIT battery [2], a s evidenced by previous publications [13,35,36]. The details of each testing item were described as below:…”
Section: Measurementsmentioning
confidence: 99%
“…Vigorous PA was also found beneficial to CRF, a s children who accumulated 40 min vigorous PA was greater than those only had 18 min [44]. Further, longitudinal studies showed PA was positively correlated with CRF, musculoskeletal fitness, a n d motor fitness in preschool children [35,45]. To date, no empirical study has examined the associations between daily step counts and physical fitness in preschool children.…”
Section: Comparison With the Findings From The Previous Publicationsmentioning
confidence: 99%